Persepsi Remaja tentang Perilaku Seksual di Desa Rogo Kecamatan Dolo Selatan Kabupaten Sigi: Adolescents’ Perceptions of Sexual Behavior in Rogo Village, South Dolo Subdistrict, Sigi Regency - Nursan; Mudaimin, Mudaimin; Samintang (Program Studi Tadris Ilmu Pengetahuan Sosial (TIPS) UIN Datokarama Palu, 2025)
This study aims to explore adolescents' perceptions of sexual behavior in Rogo Village, Dolo Selatan District, Sigi Regency. This research employs a descriptive qualitative method with data collection techniques including observation, interviews, and documentation. The results indicate that adolescents' perceptions of sexual behavior are influenced by biological, psychological, social, and moral aspects. Adolescents mainly obtain information from social media and peers, while communication with parents and teachers remains limited. The lack of sexual education within families and schools makes adolescents vulnerable to misconceptions and increases the risk of engaging in unsafe sexual behavior. This study concludes that adolescent-friendly sexual education is urgently needed, involving the active role of parents, teachers, and the social environment to develop healthy, responsible, and morally and culturally appropriate perceptions.